Treatment of lumbar spinal stenosis with the HQ (Hernández and Quintana) interbody screw, with minimally invasive technique - Braulio Hernandez; Raymundo Quintana; Carlos Montes; Roberto Cantú; Eduardo Modiano (International Journal of Spine Research - Peertechz Publications, 2020)
Lumbar spinal stenosis is a frequent ailment that affects people over 50years. With previous studies by J. Zucherman, and the cadaveric investigations with maximum flexion and extension by W. Rauschning, it was demonstrated that the bulging of the posterior longitudinal ligament and the ligamentum flavum were the main causes of radicular compression; but, the key aspect was that once the interbody space was expanded, the compression was relieved. However, a posterior stabilization and an interbody arthrodesis must be performed.  In this study there were 128 patients divided in 2 groups; the technique was to introduce interbody spacers through Kambin's triangle.  In the first group, the interbody space was opened with Zeus peek spacers, and in the second group the titanium HQ (Hernández and Quintana) screw was used.  The results were good in 85% of the patients with the peek spacers, and 90% for the second group with the HQ screw. It was found that the screw spacers were much more stable than the regular spacers, thus presenting far less complications.